Pengaruh Orientasi Pasar Terhadap Distinctive Capability dan Implikasinya pada Keunggulan Bersaing UMKM Kota Bandung Sebagai Industri Kreatif (Survei Pada Empat Sentra UMKM Unggulan Kota Bandung) - LISNAWATI (2010)
ABSTRACT Lisnawati 0808666, "The Influence of Market Orientation Concering Distinctive Capability In The Direction of Implication to Competitive Advantage SME's Bandung City as a Creative Industry (Research in Four Bandung Small Medium Enterprises/SMEs Considered to center of Superiority) Guidance by Dr. Hj. Ratih Hurriyati M.Si and Dr. Lili Adi Wibowo, S.Sos., S.Pd, M.M. The effort of Indonesian valued still lowless, it indicate that every single competition bettwen other industry and another secor hasn't maximum in every nation, power of SME is very important because we can make a great competition to increase ever invention, moreover foreign exchange the uncompetitive of SMEs in Indonesia, happening by unrecovery of a good distinctive capability yet. According to the phenomenon, this thesis focused on examine market orientation to increase distinctive capability and the implication to Competitive Advantage SMEs in Bandung. In order to method used to by descriptive survey and explanationary survey for 100 respondent SMEs as four biggest center in Bandung, and this research doing in a year ago so another method that I can used is cross sectional method. For process bout data, I used primary and secondary data that collective by drivining manual to the library then quetionare whereas for measure how important the impluence market orientation to distinctive capability and impact to finance used to by SEM analysis. The result will show about activity of market orientation, has influence and positive impact to distinctive capability and also to competer. We can conclude, that more higher distinctive capability will make the condition of Competitive each SMEs in Bandung more higher too. Additionally, market orientation will increase distinctive capability and competitive advantage SMEs in Bandung.